Bentuk Dan Fungsi Sanggar Pamujan Bangunan Pertapaan Raja Keraton Gungung Kawi Kabupaten Malang - Setiawan, Jodi (Universitas Indraprasta PGRI, 2023)
This study aims to analyze the structure and function of the Pamujan Palace building, Keraton Gunung Kawi, Malang Regency. The object of this research is the form and function of the Sanggar Pamujan building, the tallest building in the Gunung Kawi Palace. The theory used to analyze is the theory of structuralism. Structuralism theory is a theory that studies and understands the subconscious mind of humans living their lives with myths to find out the relationship and function with cultural structures. This research method uses descriptive qualitative which describes and interprets the meaning of the data that has been collected and then studied and understood so as to obtain general and comprehensive conclusions. The data are in the form of interview words from the caretaker and supporting documentation data. The collected data is then analyzed, interpreted. The result is a triangular mountain which means a place that is considered sacred from the realm of life to death. The two statues in the form of a sembrani horse mean a vehicle to heaven. The three square shapes of the building mean that the five pancer sedulur papat are the four corners of the winds with the elements of water, fire, wind, and earth to protect from negative things. Its functions are, Chess boarding four levels of human life in the phase of leaving the world, Tri Hita Karana the concept of connecting with God for happiness and peace, and Astanga Yoga a way of connecting with God through meditation on physical and spiritual control with God.